2017
DOI: 10.1177/0954410017725544
|View full text |Cite
|
Sign up to set email alerts
|

Design and manufacture of nacelles for small turboprop aircraft

Abstract: The aim of this paper is to present the results of prepreg nacelles design and manufacturing for I-31T aircraft. The work was part of the European Union project ‘Efficient Systems and Propulsion for Small Aircraft’ (ESPOSA). The new engine cowling design was preceded by computational fluid dynamics numerical analyses stage. Use of TP100 engine was assumed, which was installed on the I-31T aircraft in the framework of the ESPOSA project. This article presents the process of external geometry adjustment, chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…I-31T is based on the piston I-23 design. Nacelle with composite cowlings [3] was designed to incorporate turboprop engine TP100 that replaced old piston 0-360-A1A engine. New engine mount geometry was optimised to minimise its weight [4].…”
Section: Tp100 Engine-airframe Integrationmentioning
confidence: 99%
“…I-31T is based on the piston I-23 design. Nacelle with composite cowlings [3] was designed to incorporate turboprop engine TP100 that replaced old piston 0-360-A1A engine. New engine mount geometry was optimised to minimise its weight [4].…”
Section: Tp100 Engine-airframe Integrationmentioning
confidence: 99%
“…The installation of new TP100 turbine engine and new avionics in the aircraft required a thorough redesign of the cockpit and front part of the fuselage (new engine necelles), (Dudziak et al , 2017). The project involved a construction of digital displays for navigation systems and monitoring the work of the engine in the form most approachable for the pilot.…”
Section: Project Purposementioning
confidence: 99%
“…Of course, a lot of helpful studies can be found, but these always describe specific cases and give one partial knowledge that must be combined in the designer's mind to reach a satisfactory result. 510…”
Section: Introductionmentioning
confidence: 99%